Efficacy and safety of Ginkgolide with intravenous alteplase thrombolysis in acute ischemic stroke with large vessel occlusion: a subgroup analysis of GIANT - Zhang, Zheyu; Zhong, Wansi; Zhang, Xuting; Ma, Xiaodong; Lu, Xudong; Zhang, Meixia; Tao, Anyang; Zhang, Bing; Lou, Min (Frontiers in Pharmacology, 2024)
Aim: To explore the effectiveness and safety of Ginkgolide ® in acute ischemic stroke (AIS) patients with large vessel occlusion (LVO) and moderate-to-severe stroke receiving intravenous alteplase thrombolysis (IVT).Improving Neurological Function (GIANT) was an open label, prospective, multicenter cluster-randomized clinical trial and included AIS patients in 24 centers randomized to intervention of intravenous Ginkgolide ® or control group within the first 24 h after IVT. LVO was defined as any occlusion of internal carotid artery, M1 or M2 of middle cerebral artery, A1 or A2 of anterior cerebral artery, P1 of posterior cerebral artery, V4 of vertebral artery or basilar artery.Stroke severity was assessed with National Institutes of Health Stroke Scale (minor ≤5; moderate-to-severe >5). Primary outcome was a good outcome, defined as a modified Rankin Scale (mRS) of, 0-2 at 90 days. Secondary outcomes were early neurological improvement (ENI) defined as ≥18% increase of National Institutes of Health Stroke Scale (NIHSS) score at 7 days compared to baseline and distribution of mRS at 3 month.Results: A total of 1,113 patients were included, with 268/913 (29.4%) presenting LVO and 508 (45.6%) presenting moderate-to-severe stroke. In patients with LVO, Ginkgolide ® usage was independently associated with ENI (P = 0.001), but not with good outcome (P = 0.154). In moderate-to-severe subgroup, Ginkgolide ® was independently associated with both good outcome (P = 0.009) and ENI (P = 0.028). Ginkgolide ® did not increase the risk of hemorrhagic transformation (all P > 0.05).Using Ginkgolide ® within 24-hour after intravenous rt-PA is effective and safe in LVO and moderate-to-severe stroke patients.